2015
DOI: 10.1002/mds.26227
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor processing for balance in spinocerebellar ataxia type 6

Abstract: BackgroundWe investigated whether balance impairments caused by cerebellar disease are associated with specific sensorimotor processing deficits that generalize across all sensory modalities. Experiments focused on the putative cerebellar functions of scaling and coordinate transformation of balance responses evoked by stimulation of single sensory channels.MethodsVestibular, visual, and proprioceptive sensory channels were stimulated in isolation using galvanic vestibular stimulation, moving visual scenery, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Interestingly, in patients with spinocerebellar ataxia type 6, in spite of clear-cut increase in body sway, habituation properties to new visual, vestibular, and proprioceptive inputs were not different from controls for all three sensory modalities [24], again indicating that temporal aspects of sensory integration may not be accomplished by the midline cerebellum. Imaging studies in humans and single cell recordings in primates underscore the prominent role of the premotor and parietal cortices [8385] and the striato-pallido-thalamo-cortical circuit [86] as sensorimotor interface, supporting the hypothesis that these structures might be involved in the mechanisms of shifting the reference frame on the basis of the available sensory information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in patients with spinocerebellar ataxia type 6, in spite of clear-cut increase in body sway, habituation properties to new visual, vestibular, and proprioceptive inputs were not different from controls for all three sensory modalities [24], again indicating that temporal aspects of sensory integration may not be accomplished by the midline cerebellum. Imaging studies in humans and single cell recordings in primates underscore the prominent role of the premotor and parietal cortices [8385] and the striato-pallido-thalamo-cortical circuit [86] as sensorimotor interface, supporting the hypothesis that these structures might be involved in the mechanisms of shifting the reference frame on the basis of the available sensory information.…”
Section: Discussionmentioning
confidence: 99%
“…It is also involved in processing self-motion perception [19, 20 for a review] and in the control of stance under critical conditions [21]. In keeping with these notions, standing balance deteriorates with age-related shrinkage of the vermis [22]; it is impaired in individuals with degenerative cerebellar disease, including spino-cerebellar ataxia [23, 24] and in chronic alcoholism, in which sway path length is selectively related to the volume of the vermis [25, 26]. …”
Section: Introductionmentioning
confidence: 99%
“…Dynamic SVV tasks have shown that large-field angular visual motion can bias orientation perception as if the head were tilted relative to gravity (Dichgans et al, 1972; Held et al, 1974). The effect of large-field angular visual motion on SVV and postural reorienting increases with age, and is accentuated in some cerebellar disorders (Kobayashi et al, 2002; Bunn et al, 2015). For example, large-field angular visual motion heavily biases SVV and elicits abnormally large postural sway in patients with spinocerebellar ataxia type 6 (Bunn et al, 2015; Dakin et al, 2018).…”
Section: Visual Motion Cues Signal Changes In Head Tiltmentioning
confidence: 99%
“…The effect of large-field angular visual motion on SVV and postural reorienting increases with age, and is accentuated in some cerebellar disorders (Kobayashi et al, 2002; Bunn et al, 2015). For example, large-field angular visual motion heavily biases SVV and elicits abnormally large postural sway in patients with spinocerebellar ataxia type 6 (Bunn et al, 2015; Dakin et al, 2018). Neural representations of large-field angular visual motion, which may contribute to head orientation estimates, have been identified in multiple brain regions of monkeys, including the cerebellum (Kano et al, 1990, 1991), brainstem (Waespe and Henn, 1977), and ventral intraparietal area (Sunkara et al, 2016).…”
Section: Visual Motion Cues Signal Changes In Head Tiltmentioning
confidence: 99%
“…Posturography was additionally used to explore levels of axial instability. Laboratory investigations of sensory mechanisms of balance control (dynamic conditions) have incorporated the use of posturography in order to determine sensorimotor abnormalities in adults with SCA6 . Posturography requires careful control of sensory conditions to ensure reliability of highly sensitive measures, but, when achieved, is feasible as a measure to either track disease progression or to evaluate the treatment effect of therapies in both clinical and home settings .…”
Section: Methodsmentioning
confidence: 99%